2018
DOI: 10.1590/1980-5373-mr-2016-1111
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Chemical Effects of Plasma Treatment with Oxygen (O2) and Sulfur Hexafluoride (SF6) on Cellulose Surface

Abstract: Cellulose is a polymer widely available in nature, however its applications may be restrict due to its hydrophilic character. The creation of hierarchical structures on the surface is one of the required factors to obtain the hydrophobicity of this material. In order to compare the morphological and chemical effects caused by the action of different gases in the creation of nanostructures on the cellulose surface, samples were exposed to oxygen (O 2 ) and sulfur hexafluoride (SF 6 ) plasma treatments. The chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
(59 reference statements)
1
18
0
Order By: Relevance
“…Many techniques have been developed to render surface roughness [ 8 , 9 , 10 ] and hydrophobization. To date, the micro/nano hierarchical structures has been fabricated on the surfaces via plasma etching [ 4 , 5 , 7 , 11 , 12 , 13 ] or chemical etching [ 6 , 14 ], and plasma deposition [ 5 , 15 , 16 , 17 ], chemical vapor deposition [ 18 ], or wet coating [ 1 ] has been used to lower the surface energy. Some studies investigated the effect of the number of monofilament [ 19 ] and yarn types (filament and Drawn Textured Yarn, DTY) [ 20 ] on superhydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques have been developed to render surface roughness [ 8 , 9 , 10 ] and hydrophobization. To date, the micro/nano hierarchical structures has been fabricated on the surfaces via plasma etching [ 4 , 5 , 7 , 11 , 12 , 13 ] or chemical etching [ 6 , 14 ], and plasma deposition [ 5 , 15 , 16 , 17 ], chemical vapor deposition [ 18 ], or wet coating [ 1 ] has been used to lower the surface energy. Some studies investigated the effect of the number of monofilament [ 19 ] and yarn types (filament and Drawn Textured Yarn, DTY) [ 20 ] on superhydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…This conducting polymer has been attracted research due to its high conductivity, chemical and environmental stability, relatively easy synthesis in aqueous medium by chemical and electrochemical methods, in addition to presenting optical, electrical, and magnetic characteristics similar to semiconductor materials 9–12 . Due to its chemical structure alternated by double and single bonds, the Ppy behaves like a hybrid resonance polymer 13 . The resonance effect occurs when the Ppy solution is added to a dopant, forming paramagnetic polaronic species, which are then transformed into bipolar and, stabilized by the resonance effect in the double bonds of aromatic rings 9 …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Due to its chemical structure alternated by double and single bonds, the Ppy behaves like a hybrid resonance polymer. 13 The resonance effect occurs when the Ppy solution is added to a dopant, forming paramagnetic polaronic species, which are then transformed into bipolar and, stabilized by the resonance effect in the double bonds of aromatic rings. 9 Fe 3 O 4 -np and Ppy have been widely applied in countless studies, which demonstrate numerous synergistic properties.…”
mentioning
confidence: 99%
“…Besides, plasma has a sterilization functionality as well as chemical and morphological modification efficacy (Vogler, ). Changes followed by plasma exposure, affect a thin layer of surface depends on some variables involving applied power and the time of exposure to the precursor gas combination, which directly affect the resultant exposed surface (Camargo, de Rangel, da Cruz, de Menezes, & Delgado‐Silva, ). Plasma technique could commercialized owing to numerous advantages such as flexible specifications of plasma and desirable cell response (Lee & Yang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mentioned recovery phenomenon followed by oligomers migration from the bulk toward the surface and surface polar groups’ reorientation in the opposite direction within some hours which plasma treated PDMS samples are in ambient condition (Almutairi, Ren, & Simon, ; Kim & Jeong, ; Lee & Yang, ). Some investigations assigned to prolong the hydrophilic stability induced by O 2 plasma on the PDMS surface in different ways like storing treated films in an aqueous medium (Camargo et al, ). In a similar study, Ten et al employed O 2 plasma at 70 W for several time durations and demonstrated hydrophilicity never fully recovers over the time duration of experiment but it saw a descending trend (Tan et al, ).…”
Section: Introductionmentioning
confidence: 99%